Women as unseen characters : male ritual in Papua New Guinea - Bonnemere, Pascale (Social anthropology in Oceania., 2004)
Rituals have always been a focus of ethnographies of Melanesia, providing a ground for important theorizing in anthropology. This is especially true of the male initiation rituals that until recently were held in Papua New Guinea. For the most part, these rituals have been understood as all-male institutions, intended to maintain and legitimate male domination. Women's exclusion from the forest space where men conducted most such rites has been taken as a sign of their exclusion from the entire ritual process.Women as Unseen Characters is the first book to examine the role of females in Papua New Guinea male rituals, and the first systematic treatment of this issue for any part of the world. In this volume, leading Melanesian scholars build on recent ethnographies that show how female kin had roles in male rituals that had previously gone unseen. Female seclusion and the enforcement of taboos were crucial elements of the ritual process: forms of presence in their own right.Contributors here provide detailed accounts of the different kinds of female presence in various Papua New Guinea male rituals. When these are restored to the picture, the rituals can no longer be interpreted merely as an institution for reproducing male domination but must also be understood as a moment when the whole system of relations binding a male person to his kin is reorganized. By dealing with the participation of women, a totally neglected dimension of male rituals is added to our understanding.